Evaluating the Probability of Previously Unknown Carriage of MRSA at Hospital Admission - Harbarth, Stephan; Sax, Hugo; Fankhauser-Rodriguez, Carolina; Schrenzel, Jacques; Agostinho, Americo; Pittet, Didier (The American journal of medicine, 2006)
We determined the prevalence and risk profile of patients with previously unknown carriage of methicillin-resistant Staphylococcus aureus (MRSA) at hospital admission. We conducted a 7-month, prospective case-controlled study in adult inpatients admitted to a university hospital with endemic MRSA. Multivariate conditional logistic regression for data sets matched 1:4 was performed to identify the risk profile of newly identified MRSA carriers. Overall, 399 of 12 072 screened admissions (prevalence, 3.3%) were found colonized (n = 368, 92%) or infected (n = 31, 8%) with MRSA. In 204 cases (prevalence, 1.7%), MRSA carriage was newly identified. Without screening on admission, 49% (196/399) of MRSA carriers would have been missed. We identified nine independent risk factors for newly identified MRSA carriage at admission (adjusted odds ratio): male sex (1.9); age greater than 75 years (2.0); receipt of fluoroquinolones (2.7), cephalosporins (2.1), and carbapenems (3.2) in the last 6 months; previous hospitalization (1.9) or intravenous therapy (1.7) during the last 12 months; urinary catheter at admission (2.0); and intrahospital transfer (2.4). A risk score (range, 0-13) was calculated by adding points assigned to these variables. On the basis of analysis of 1006 patients included in the case-controlled study, the probability of MRSA carriage was 8% (28/342) in patients with a low score (≤1), 19% (92/482) in patients with an intermediate score (2-4), and 46% (84/182) in patients with a high score (≥5). The risk score had good discrimination (c-statistic, 0.73) and showed excellent calibration ( P = .88). On-admission prevalence of previously unknown MRSA carriers was high. Applying the risk score to newly admitted patients with an intermediate or high probability of MRSA carriage could allow a more effective MRSA control strategy.